N'Dama cattle production in relation to nutritional interventions in villages in The Gambia - Riley, J.A.; Agyemang, K.; Dwinger, R.H.; Jeannin, P.; Grieve, A.S.; Little, D.A. (ILCA/ILRAD, 1988)
Presents the results of feeding trials in three villages in Gambia, viz, Keneba, Pirang & Nioro Jattaba, conducted to assess responses during the dry season to small inputs of a protein supplement in recently calved cows and in young suckling calves.